The Relationship Between Religion and the State for the Sovereignty of the NKRI Study of Suryalaya TQN Murshid Thought in the Tanbih Text - Dodo Widarda (Jurnal Studi Sosial dan Politik, 2020)
The research aims to search and find the relationship between religion and the state in the Text of the Tanbih of the Tarekat Qodiriyyah wa Naqsyabandiyyah (TQN) Suryalaya. This type of research is qualitative research through factual historical research on manuscript texts with the Philosophy Research Methodology. In the Tanbih Text originating from Sheikh Abdullah Mubarak bin Nur Muhammad (Abah Sepuh) and later popularized by Sheikh Ahmad Shohibul Wafa 'Tajul' Arifin (Abah Anom) the relationship between religion and the state has significant significance and serves as a guide for community and state life for the brothers TQN. In addition to developing Islamic values, Tanbih directed the brothers to develop a feeling of love for the motherland. The conclusion of this research, there is a strong relationship between religion and the state in the Tanbih Text and can be the basis for maintaining the sovereignty of the NKRI with a strong religious perspective. This study provides recommendations for further research related to the relationship of religion with the state to strengthen the mandate of Indonesians amid the development of various ideologies that threaten state sovereignty.